Analisis Gugatan Wanprestasi dalam Jual Beli Tanah (Studi Putusan Nomor: 127/Pdt.G/2014/ PN.TK) - Tami Rusli (PRANATA HUKUM, 2016)
The legal act of buying and selling is one of the legal issues in the land sector. The sellers must submit property rights of the goods to the buyer. The research problem is a basic consideration of the judge ruled on a lawsuit breach of contranct by land of buying and selling in Decision No. 127 / Pdt.G / 2014 / PN.TK. Normatif juridical approach and empirical. Collecting data with literature studies and field studies, qualitative data analysis. The research result shows that the basic considerations in deciding the lawsuit breach of contract judges buying and selling land is optimal and meets the principles of justice where the defendant has fulfilled all obligations within the agreed payment. The breach of contract by the Plaintiff is not reasonable because land sales conducted in 2008 was melting giro The new conducted in 2010, and a description of the refusal of Bank BRI KC Telok Betong caused receiver EFD Debit is not accompanied by an acceptance of physical Debit certificate / Debit certificate is lost, not because there are no funds (empty). Suggestions submitted in a civil action must include proof of the original letter.